Mental health status of individuals with sexual development disorders: A review. Issue 4 (August 2019) - Bohet, M.; Besson, R.; Jardri, R.; Manouvrier, S.; Catteau-Jonard, S.; Cartigny, M.; Aubry, E.; Leroy, C.; Frochisse, C.; Medjkane, F.
Summary: Healthcare recommendations for people with disorders of sexual development (DSDs) include mental health attention and active participation of psychiatrists and psychologists in dedicated multidisciplinary teams. Therefore, it seems crucial for them to improve knowledge about specific difficulties and needs of these patients. The aim of this article is to report in a synthesizing manner the recent works evaluating the mental health and psychological status of individuals with DSDs. After research conducted using PubMed and ScienceDirect, 18 studies were inventoried and qualitatively analyzed in response to three main questions: Do individuals with DSDs suffer more frequently and/or more severely from psychological conditions or mental disorders? From what kind of disorder do they suffer? and What are the determinant factors involved in their development? This work highlights an increased risk of affective disorders in individuals with DSDs, particularly anxiety and depressive disorders and interpersonal difficulties. Studies identified some potentially determining factors implicated in their development, among which are the etiology of DSDs, the life stage, the age at the time of diagnosis, and the lack of conformity of sexual phenotype with sex assignment. Taken together, the etiology of DSDs, the lack of conformity of sexual phenotype with sex assignment, and the feeling of being different from peers seem to be interesting factors to study in the future. Multicentric and longitudinal studies using standardized evaluation and control groups should be the most robust way to improve knowledge about these preoccupations.